AB0151 Environmental pollution and systemic sclerosis: a pilot study on benzene and particulate exposure as risk factors for the systemic manifestations. (23rd January 2014) - Bosello, S. L.; Bocci, M.; Poscia, A.; Colaiacono, G.; La Milia, D.; De Luca, G.; Berardi, G.; Rucco, M.; Correra, M.; Canestrari, G.; Capacci, A.; Moscato, U.; et al.
Abstract : Background: The association of systemic sclerosis (SSc) with the exposure to environmental agents is supported by a number of case reports and some case-control studies. No conclusive results have been reported, but there are some evidences that exposure to vinyl-chloride-polymers (PVC), silica dust or organic solvents such as benzene (B) and xylene (X) may be implicated. Furthermore a higher prevalence of scleroderma in boroughs in close proximity to a major airport, has been reported, but few data on air pollution exposure and risk of systemic sclerosis are available. Recently, particulate air pollution has been consistently linked to increased risk of arterial cardiovascular disease. Objectives: We studied relationships between outdoor concentration of B and particulate with clinical manifestations of SSc based, for the exposure, on the urban residence of patients. Methods: Before patient administration, the questionnaire was validated by Delphi technique (4 rheumatologists, 4 statisticians and 2 common people). A cohort study of 88 SSc patients, filled the validated self administered questionnaire (analyzing drug, work and environmental exposure) to investigate potential risk exposure before and after the onset of the disease. The average mean concentrations of B (11 monitoring sites) and environmental particulate matter with aerodynamic diameter ≤ 10 μm(PM10 ) (14 sites) were computed using data from monitors located throughout the Lazio region, in Italy. In a sample of 33 patients we performed correlations between the concentrations of PM10 and B with the demographic and clinical characteristics, going back to a prior exposure of 2 years before the onset of Raynaud's phenomenon (RP). Results: The questionnaire resulted in an agreement of the overall experts of about 94% (according to11/190 disagreement for comprehension, only few lexical modifications were done to improve the questionnaire after the consensus between the experts), with an Inter-observer agreement (measured throughout K Cohen test) of 0.8019(p<0.01) showing a very good concordance. The mean disease duration from the RP onset was 13.0±9.4 years and the mean age was 55.0±12.9 years. 92.5% of patients were female. No correlations were found between different clinical disease characteristics and drug assumption and work exposure. Considering patients that lived in Lazio, SSc patients with diffuse skin disease were exposed 2 years, before the onset of RP, to a higher concentrations of benzene (8.5±1.5µg/m 3 ) with respect to patients with limited skin disease (4.97±2.7µg/m 3 ), which was statistically significant of p=0.02. Furthermore the concentrations of benzene correlated directly with the skin score (R=0.3, p≤0.05) and inversely with DLCO (R=-0.36, p≤0.05). SSc patients with ulcers were exposed 2 years before the onset of RP to higher concentrations of B (6.4±3.2 µg/m 3 ), than the patients without ulcers (4.9±2.3µg/m 3 ), but the difference did not reach statistical significance. Conclusions: This study, on the role of environmental agents in the manifestations of SSc, suggests an increased exposure to benzene in the development of a diffuse skin disease and a possible predisposing effect on the occurrence of ulcers. Disclosure of Interest: None Declared